Expression of Aspergillus oryzae asparaginase in yeast Pichia pastoris - Ngoc, Nguyen Thanh; Lam, Le Tung; Dung, Nguyen Thi; Huyen, Do Thi; Huong Tra, Nguyen Thi; Hai, Truong Nam (Academia Journal of Biology, 2014)
Total 13 rare codons in gene encoding asparaginase from Aspergillus oryzae were replaced with the most frequent ones for Pichia pastoris. The optimized gene (asp1) was synthesized and cloned into pUC57 then inserted into pPIC9 at XhoI-NotI cleavage site to generate pPIC9-asp1. After digestion with StuI, pPIC9-asp1 was transformed into P. pastoris cells by electroporation. All four investigated recombinant P. pastoris clones had Mut+ phenotype that were able to grow in medium containing methanol as sole carbon source. In medium containing 0.5% methanol, the recombinant P. pastoris harboring asp1 gene started producing asparaginase at 21th hour. The amount of ASP1 increased steadly and reached plateau after 54 hours of cultivation.  In the native polyacrylamide gel without SDS, ASP1 presented in dimer form of ~ 100 kDa and exhibited activity to hydrolyze asparagine into aspactate and ammonia. This is the first report on expression of A. oryzae asparaginase in P. pastoris. This study will faciliate researches on production of commercial asparaginase for food industry.